The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep30748
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognosis of omental gastrointestinal stromal tumor: evaluation of a pooled case series

Abstract: Clinicopathological features and prognosis of omental GISTs are limited due to the extremely rare incidence. Therefore, the aim of the present study was to investigate the clinicopathological features and prognosis of omental GISTs. Omental GISTs cases were obtained from our center and from case reports and clinical studies extracted from MEDLINE. Clinicopathological features and survivals were analyzed. A total of 99 cases of omental GISTs were enrolled in the present study. Omental GISTs occurred predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…The median tumor size was 9.0 cm (range: 2.6-30.0 cm) and the median mitotic rate was 5.0/50HPF. In this study, the main clinical presentations were abdominal mass in 14 cases, abdominal distention and pain in 6, detected by healthy screening in one, spontaneous rupture of tumor and intra-abdominal hemorrhage in one, and synchrous liver metastasis was in one case at the time of diagnosis, which is similar to the literature report [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Also, our study revealed that the tumor size was 6.8cm (ranging from 4.0cm to 22.0cm), including 2 cases with tumor <5cm in diameter, 6 with tumor size between 5 to 10cm, 14 with tumor> 10cm, this results suggested the most EGISTs were very advanced disease at diagnosis, difficult to diagnose in early stage.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The median tumor size was 9.0 cm (range: 2.6-30.0 cm) and the median mitotic rate was 5.0/50HPF. In this study, the main clinical presentations were abdominal mass in 14 cases, abdominal distention and pain in 6, detected by healthy screening in one, spontaneous rupture of tumor and intra-abdominal hemorrhage in one, and synchrous liver metastasis was in one case at the time of diagnosis, which is similar to the literature report [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Also, our study revealed that the tumor size was 6.8cm (ranging from 4.0cm to 22.0cm), including 2 cases with tumor <5cm in diameter, 6 with tumor size between 5 to 10cm, 14 with tumor> 10cm, this results suggested the most EGISTs were very advanced disease at diagnosis, difficult to diagnose in early stage.…”
Section: Discussionsupporting
confidence: 86%
“…In 95% of EGIST cases, the CD117 protein exhibits a strong, diffuse positive immunohistochemical reaction, and 60-70% of EGISTs were CD34-positive [2][3][4]. Feng et al [12] reported the positive rates of CD117, CD34 and DOG-1 were 84.5%, 83.7% and 88.9%, respectively. An immunochemical study of EGIST from Reith et al [9], revealed that the tumors expressed CD117 (100%), CD34 (50%), NSE (44%), SMA (26%), desmin (4%), and S-100 protein (4%).…”
Section: Histopathological Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…It is considered to originate from interstitial cells of Cajal, the pacemaker cells of GI tract [2]. Histologically, the most common cell morphology was spindle, followed by epithelioid and mixed phenotype [3].…”
Section: Introductionmentioning
confidence: 99%